TERPENOIDS OF MATRICARIA CHAMOMILLA L. FROM DIFFERENT PLACES OF GROWTH - Titova Natalya Gennad’evna; Shamilova Saltanat Talgatovna; Zhabayeva Anar Nikhanbaevna; Adekenov SergazyMynzhasarovich (Academic Scientific Journal of Chemistry, 2019)
In this work, a comparative gas chromatography-mass spectrometry analysis of the component composition of CO2-extracts from Matricaria сhamomilla L. raw materials collected at the site of medicinal plants of the International Research and Production Holding “Phytochemistry” (Karaganda region, Republic of Kazakhstan), Mozheikovo agro-town (Grodno Region, Belarus) and in the vicinity of Sarkand (Almaty region, Republic of Kazakhstan) was undertaken. As a result of the research conducted, it was revealed that the major components of the obtained CO2-extracts of Matricaria сhamomilla L. are: bisabolol oxide A, bisabolol oxide B and en-in-dicycloether. Meanwhile, in the CO2-extract of Matricaria сhamomilla L. collected at the site of medicinal plants of JSC “IRPH “Phytochemistry”the quantitative content of matricarin and chamazulene are prevailed.Thus, thecontent of matricarin exceedthree times, and the content of chamazulene five and two times, in comparison with extracts obtained from the Belarusian and Almaty raw materials. The prospect of using Matricaria сhamomilla L. raw material that grows on the medicinal plants site of JSC “IRPH “Phytochemistry” in the production of the anti-inflammatory ointment “Matripin-Dent” has been established.